Structural basis of dialogue between science and religion in the modern context - Шашкова, Л.О. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The article describes the basic model and characterize the relationship between science and religion, and reasonable grounds for their constructive dialogue in the cultural context of modernity.